Development of E-Book Based Volleyball Learning Model - Dewi Endriani; Imran Akhmad; Basyaruddin Daulay (UNIB Press, 2022)
Based volleyball learning model e-book- and developed it as a sports lecturer's guide in teaching courses volleyball The resulting products are learning models volleyball learning materials volleyball based E-Book-. This research was developed by adapting the Borg & Gall educational research and development model. The development procedure used includes several stages: 1) recognizing the content of the product being developed, 2) developing the initial product of the game, 3) expert validation, 4) testing field The data analysis technique used in this research is done in two ways, namely quantitative and qualitative. Based on media trials in the field, the following results were obtained: 1) The media developed was very valid (good) with an average media validation questionnaire by experts of 92.39%. 2) The learning media developed is very practical, by getting a very good response where the average questionnaire is 92.12% which gives a positive response, 3) the E-Book media developed is quite effective, where the completeness of student learning outcomes reaches 87.19 %. From these results, it shows that the animation-based E-Book media that was developed is very feasible to be used in supporting learning activities in the classroom.